Sistem Navigasi Automated Guided Vehicle Berbasis Computer Vision dan Implementasi pada Raspberry Pi - Florentinus Budi Setiawan; Oei Jevon Aldo Wijaya; Leonardus Heru Pratomo; Slamet Riyadi (Jurnal Rekayasa Elektrika, 2021)
In the current technological development era, many companies compete to produce robots that can help humans work significantly to streamline time and energy in creating an item. One of the robots being developed in this industrial area is Automated Guided Vehicle (AGV). AGV is a robot for transporting goods whose path and direction automatically. This journal will discuss the navigation system and mobility on the AGV. They are using four-wheel type Omni wheels and a DC motor as a drive. The wheel is used to adjust the direction of motion both forward, backward, right, and left. For movement settings automatically, controlled via computer vision. Using  the navigation system by following a pattern in the form of instructions using the camera as a sensor to determine the current AGV. Due to the nature of the navigation method employed, the yield of vehicle trails can be very suboptimal, especially in messy warehousing environments.